Bancassurance : Prospects, Strategies, Challenges and Mutual Benefits - Sridharan, G.; Allimuthu, S. (Indian Journal of Finance, 2009)
One of the most significant changes in the financial services sector over the past few years has been the growth and development of bancassurance. With the opening up of Insurance Industry for foreign investments the state owned insurance companies are facing tough competition. The competition is growing with the entry of global players having variety of insurance schemes to tap huge market available. These insurance companies involve in various strategic decisions to grow with alliances, joint ventures, and consolidation. Banks in India have a wider network with high level of confidence and trust among public. This made insurance companies to have distribution agreements with banks. The introduction of bancassurance concept the banks with the customer base they have are able to tap the market very well.Banking institutions and insurance companies have found bancassurance to be an attractive and profitable complement to their existing activities. The successes demonstrated by various bancassurance operations particularly in Europe have triggered an avalanche of mergers and acquisitions across continents and efforts are on to replicate the early success of bancassurance in other parts of the world as well.